2021
DOI: 10.1111/geb.13378
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric models of microbial metabolic limitation in soil systems

Abstract: Aim: Ecoenzymatic stoichiometry provides a promising avenue for deciphering resource constraints on soil microbial metabolism but is hampered by limitations in current modelling techniques.Innovation: Herein we developed new models for quantifying microbial metabolic limitations based on the stoichiometric and metabolic theories of ecology, using an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 85 publications
(179 reference statements)
4
67
0
Order By: Relevance
“…These results indicated that microbial P limitation occurred after converting cropland to forest. Similarly, under the same OC level (< 10 g kg -1 ), the VT N/P limitation value was close to or less than zero in agriculture and grassland ecosystems but greater than zero in forest ecosystems at global scale (Cui et al 2021). Xu et al…”
Section: Effects Of Cropland Revegetation On Microbial Metabolic Limi...mentioning
confidence: 83%
See 1 more Smart Citation
“…These results indicated that microbial P limitation occurred after converting cropland to forest. Similarly, under the same OC level (< 10 g kg -1 ), the VT N/P limitation value was close to or less than zero in agriculture and grassland ecosystems but greater than zero in forest ecosystems at global scale (Cui et al 2021). Xu et al…”
Section: Effects Of Cropland Revegetation On Microbial Metabolic Limi...mentioning
confidence: 83%
“…EEAC: CBH+BG; EEAN: NAG+LAP; EEAP: AP. Cropland a , Forest a ; and Grassland a were from Cui et al (2021) at global scale. Detailed information was in Table S2.…”
Section: Discussionmentioning
confidence: 99%
“…We observed the ratio of the natural logarithm of C-, N-, and P-acquiring enzymes is approximately 1.3:1.3:1 in this study, which diverged from the ratio of 1:1:1 on a global scale ( Sinsabaugh et al, 2009 ). Cui et al (2021) revealed the relationships of C:N:P-acquiring enzyme activities far from the widely recognized mean ratio of 1:1:1 in different ecosystems. Low-concentration P fertilizers addition resulted in the drift of the ratio to 1.2:1.3:1, indicating that microorganisms are still co-limited by C and N ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 93%
“…Microbial communities may be subject to diverse restrictions on soil nutrients under different environmental conditions ( Cui et al, 2021a ). TER L can be used to identify which element has the strongest limitation for microbial community growth ( Cui et al, 2021b ). In this study, microbial metabolism was N-limited at the early stage of vegetation restoration (< 31 years) and the microbial N limitation decreased significantly, thereafter shifted to microbial P limitation ( Figure 3C ).…”
Section: Discussionmentioning
confidence: 99%
“…TER L model defines the microbial N or P limitation by scaling the TER. We calculated a new TER model (TER L ) to identify which nutrient has the strongest limitation with the following equations ( Cui et al, 2021b ):…”
Section: Methodsmentioning
confidence: 99%